Side by Side We Stand - deLeon, Paige (Office of the Prime Minister TT, 2012)
This publication is intended to invoke a sense of nostalgia, a feeling of warm recollection and an invitation to converse with the children of Trinidad and Tobago about the events and the people these photos have captured.